Sosialisasi pemanfaatan sistem informasi keuangan toko sembako bu Riya di Kelurahan Banyu Urip Surabaya - Mukhtar Adinugroho; Teguh Herlambang; Firman Yudianto; Afiananda Rizky; Leni Yuliana (UKInstitute, 2024)
The grocery store business is currently very promising for entrepreneurs who are currently involved in the business economy. This business has many enthusiasts due to its unique concept with customers being free to choose the type of product they sell themselves. If you look at the competitors, there are quite a lot and each shop has its own advantages over the others. One of the differences that can be seen is on the management side, various variations or methods are used to increase productivity from the management side, which include recording existing product stock, calculating expenditure and calculating input. This will be the key to the success of management in carrying out processing because when these things are not done well it will result in the emergence of new problems. Therefore, the service activities carried out at the Bu Riya grocery store are to help with these problems using an approach method that includes planning, implementation and evaluation stages. The stages that have been carried out in planning are able to create a plan to resolve problems in stall management such as recording and the flow of money in and out. After that, the implementation method itself is implemented, namely by implementing what has been identified by creating a management application solution. From the entire series of activities carried out, a new management process was obtained by digitizing several aspects such as recording product stock and managing the flow of cash in and out. The digitalization that has been implemented is based on Android and significant results have been obtained, namely that operational shop management is able to use it well.